Levelling of i-umlaut in classical and post-classical Old Frisian nouns - Buczek, Katarzyna (Penerbit Universiti Kebangsaan Malaysia, 2022)
The paper discusses and evaluates the extent of i-umlaut levelling in classical (ca. 1300–1400) and post-classical (ca.1400–1550) Old Frisian nouns. In terms of the methodology, the main goal of the analysis is to identify the quantitative relation between the incidence of i-umlauted and umlautless root vowels in the nominal declension paradigms. In order to understand and assess the process of levelling of i-umlaut in Old Frisian, three aspects that may have had an impact on the presence or absence of i-mutated vowels are taken into account, namely: the presence of the i mutation trigger *-ī and *-j and *-i, the establishment of whether i-mutation is noticeable in the entire paradigm or it is just an intraparadigmatic alternation, and finally, the differentiation between intraparadigmatic levelling of i-umlaut and borrowing from another language. A quantitative analysis is performed on the texts culled from two corpora of Old Frisian: The Corpus Oudfries and The Integrated Scientific Frisian Language Database. The analysis reveals the tendency of the language to regularize its nominal declension patterns, which results in a later levelling of i-umlauted vowels. This reveals the differentiation between the classical and postclassical period of the language’s development. Statistical tests evaluate proportion differences on the operation of i-umlaut and indicate that the discrepancies with reference to the presence of iumlauted vowels in nouns from the classical and post-classical forms are significant. The analysis and its results can supplement the study of the process and its influence on declension patterns not only in Old Frisian, but in all West Germanic languages.